The Role of Social Studies Teachers in Student Character Building Through Problem-Based E-Learning - Nasution, Syahfitri Hairani; Ponidi, Ponidi (Journal of Social Work and Science Education, 2025)
This study aims to describe the role of Social Studies teachers in building student character through the Problem-Based E-Learning (PBeL) approach in Grade IX at Budisatrya Junior High School, Medan. PBeL was selected as an innovative learning strategy that integrates contextual problem-solving with the use of digital technology in character education. This research employed a qualitative case study method, with data collected through observations, in-depth interviews, and documentation. The findings reveal that Social Studies teachers serve as facilitators, motivators, and moral guides throughout the online learning process. Through the implementation of PBeL, students are encouraged to analyze real-life social problems and present solutions collaboratively. Character values such as responsibility, tolerance, empathy, cooperation, and digital discipline developed significantly during the learning activities. Despite challenges such as limited digital literacy and technological infrastructure, teachers were able to adapt instructional strategies to remain effective in fostering character values. These findings highlight the potential of PBeL to integrate character education into digital learning while contributing to the development of a 21st-century learning model that is both humanistic and contextual. The study recommends teacher training and the strengthening of digital infrastructure to support the sustainable implementation of PBeL in secondary school character education.